New Pro-Islamic State Magazine : A Persistent Ideological Threat - Syed Huzaifah Bin Othman Alkaff (2019)
The Islamic State (IS) terrorist group, persists to propagate its ideas to the Indonesian and Malay speaking communities through its supporters in the new Hanifiyah Media magazine. Apart from spreading its ideas on religion and politics, the latest pro-IS propaganda also serves as a riposte to current counter-ideological initiatives.